The multi-shade paradox of public corruption: the Moldovan case of dirty hands and collective action - Roman, Alexandru (Crime, law and social change, 2014)
Corruption is an undoubtedly a difficult conceptual area to operate in. This is particularly accurate for the post-Soviet space, where seemingly mutually exclusive forces appear to coexist on regular basis, defying and rejecting rational interpretations. Standard assumptions, definitions and theoretical perspectives often fail to generate useful understandings of corruption in Eastern Europe, habitually obscuring fundamental patterns, hence leaving corruption largely misunderstood. In order to construct anticorruption policies that would be effective in the environment where corruption is systemic, it is critical to resist the temptation of eschewing the complexity of societal factors by over-focusing on the corrupt individual. In an effort to reemphasize the imperative role played by societal variables in explaining corruption in the post-Soviet space, this article uses insights gathered from studying corruption in Republic of Moldova to discuss the role of three fundamental dynamics: "dirty hands," the problem of "collective action" and the achromatic schema of white-gray-black corruption.